Prevalence and factors associated with overweight in adults - Brazil, 2008-2009 - Vladimir Schuindt da Silva; Israel Souza; Diego Augusto Santos Silva; Maria de Jesus Mendes da Fonseca (Universidade Federal de Santa Catarina, 2014)
The worldwide overweight prevalence showed a rapid increase in recent decades, featuring a true global epidemic. The aim of this study was to determine the overweight prevalence (BMI ≥ 25kg/m2) and possible associations with socioeconomic and demographic indicators for adults in Brazil. This epidemiological study analyzed data from the population of adults aged 20-59 years (n = 101 308 637) included in the 2008-2009 Brazilian Family Budget Survey (POF) conducted in all geographic regions of Brazil. The nutritional status assessment used the Body Mass Index, which was categorized as normal weight and overweight according to cutoff points recommended by the World Health Organization. As socioeconomic and demographic indicators, sex, age, color-race, education, income, and geographic region were analyzed. Crude and adjusted Poisson regression was performed. The results showed that the overweight prevalence was 47.7%, and the groups with the highest prevalence were adults aged 20-59 years, males, black skin color, schooling from 6 to 9 years , income of 1/4 ≥ minimum wage <1/2 and living in Southern Brazil. Almost half of adults in Brazil are overweight. Strategic actions aimed at reducing the overweight prevalence among adults in Brazil are needed to combat the obesity epidemic.